Measurement of inclusive jet production and nuclear modifications in pPb collisions at root s(NN)=5.02 TeV - Khachatryan, V. (2016)
Inclusive jet production in pPb collisions at a nucleon-nucleon (NN) center-of-mass energy of root s(NN) = 5.02 TeV is studied with the CMS detector at the LHC. A data sample corresponding to an integrated luminosity of 30.1 nb(-1) is analyzed. The jet transverse momentum spectra are studied in seven pseudorapidity intervals covering the range -2.0 < eta(CM) < 1.5 in the NN center-of-mass frame. The jet production yields at forward and backward pseudorapidity are compared and no significant asymmetry about eta(CM) = 0 is observed in the measured kinematic range. The measurements in the pPb system are compared to reference jet spectra obtained by extrapolation from previous measurements in pp collisions at root s = 7 TeV. In all pseudorapidity ranges, nuclear modifications in inclusive jet production are found to be small, as predicted by next-to-leading order perturbative QCD calculations that incorporate nuclear effects in the parton distribution functions.